Governança pública e desenvolvimento em governos locais: o perfil do gestor importa? - Silva, Clayton Robson Moreira da (2022)
In this thesis, it is argued that the public manager's profile can be decisive for the economy to move forward in a sustainable way and generate more development, with public governance being an ally in this process, since effective governance mechanisms can reduce conflicts of interest and mitigate distortions between what the citizen expects from the government and its actual actions. In this way, it is argued, in the light of the Upper Echelons Theory, that the manager's profile is associated with public governance and development in local governments. In this sense, a study is developed with the objective to analyze the relationship between manager's profile, public governance, and development in local governments. As a research context, the 184 municipalities in Ceará are analyzed, considering that local governments play an important role in political, economic, and social issues that lead a nation to development. The period investigated comprises the years 2009 to 2016, that is, two terms of municipal governments. Public governance was measured from three dimensions: accountability, efficiency, and legality. The development was investigated from a multidimensional perspective, in which economic, social, and environmental aspects are considered. Regarding the manager's profile, the following characteristics were considered: gender, age, socioeconomic status, experience, education, and political orientation. To test the research hypotheses, econometric models were estimated by the methods of Ordinary Least Squares (OLS) and Feasible Generalized Least Squares (FGLS) with panel data. The results show that public governance positively influences development in local governments. In addition, development is influenced by the following characteristics of the manager: gender, age, socioeconomic status, experience, education, and political orientation. Public governance, on the other hand, is influenced by age, socioeconomic status, experience, and education. This research findings reinforce the idea that governments with more robust governance structures and mechanisms tend to deliver better results to society, generating more development and improving the population's quality of life. From a theoretical perspective, the study provides evidence that the Upper Echelons Theory has consistency and applicability in the context of the public sector, in addition to expanding the theory by including characteristics such as political orientation. Finally, the research contributes in a social way by demonstrating that the manager's profile can be decisive for local governments to have superior results, leading citizens to reflect on the importance of taking certain characteristics into account when choosing their governors.